Acral myxoinflammatory fibroblastic sarcoma with hybrid features of hemosiderotic fibrolipomatous tumor occurring 10 years after renal transplantation. (16th June 2018) - Hallin, Magnus; Miki, Yurina; Hayes, Andrew J; Jones, Robin L; Fisher, Cyril; Thway, Khin
Myxoinflammatory fibroblastic sarcoma is a rare malignant soft tissue neoplasm that typically arises on the distal extremities of adults. It usually behaves in a low-grade manner and its characteristic histology is of a lobulated proliferation of moderately atypical spindled to epithelioid cells, vacuolated cells, and enlarged or bizarre cells with prominent nucleoli, dispersed within myxoid stroma containing a mixed inflammatory cell infiltrate. The etiology of myxoinflammatory fibroblastic sarcoma remains unknown with no definite causal factors identified. We describe a case of myxoinflammatory fibroblastic sarcoma arising in the foot of a 77-year-old female, which rapidly recurred locally after initial excision and which arose 10 years after renal transplantation. The neoplasm also showed intermingled areas of hemosiderotic fibrolipomatous tumor. The patient also had multifocal areas of squamous cell carcinoma in situ of the foot and hand, in keeping with the clinical context of immune deficiency. This is the second case of myxoinflammatory fibroblastic sarcoma reported to occur after transplantation, but additionally shows hybrid features of hemosiderotic fibrolipomatous tumor, highlights immunocompromise/immunosuppressive therapy as a possible etiologic factor in their development, and adds to the growing number of myxoinflammatory fibroblastic sarcoma that has demonstrated aggressive behavior.